ASEAN ECONOMIC COMMUNITY IMPLEMENTATION AND INDONESIAN TEXTILE INDUSTRY COMPETITIVENESS - Yuvensius Sri Susilo (Universitas Islam Indonesia, 2013)
AbstractThis study aims to analyze the impact of ASEAN Economic Community implementation in 2015 on the competitiveness of Indonesian textile and textile products industry. It uses simulations with the GTAP model to answer the proposed research questions. The GTAP simulation results suggest that Indonesian textile industry would gain the largest trade surplus followed by Thailand and Malaysia. For apparel, Vietnam would benefit the most, followed by Indonesia and Thailand. The ratio of domestic to import prices analysis suggests that Indonesian textile products have higher competitiveness than the other ASEAN’s. For the apparel products, Indonesia is as competitive as both Malaysia and the Philippines.Keywords: AEC 2015, Competitiveness, Textile dan Textile Products Industry, IndonesiaJEL Classification: C68, F15AbstrakPenelitian ini bertujuan untuk menganalisis dampak penerapan Masyarakat Ekonomi ASEAN pada 2015 pada daya saing industri tekstil dan produk tekstil Indonesia. Alat analisis yang digunakan deskriptif dan simulasi dengan model GTAP. Hasil simulasi GTAP menyarankan bahwa industri tekstil Indonesia akan memperoleh surplus perdagangan terbesar, diikuti oleh Thailand dan Malaysia. Untuk produk pakaian, Vietnam memperoleh manfaat terbesar diikuti Indonesia dan Thailand. Berdasarkan rasio harga domestik terhadap harga impor, daya saing produk tekstil Indonesia relatif lebih tinggi dibandingkan negara-negara ASEAN lainnya. Untuk produk pakaian, Indonesia kompetitif, sejajar dengan Malaysia dan Filipina.Kata kunci: AEC 2015, Daya Saing, Tekstil dan Produk Tekstil JEL Classification: C68, F15